Stainless steel wool as novel bioanode for microbial electrolysis cells: A systematic study of materials - Vázquez, Isaac; Kerzenmacher, Sven; Santiago, Óscar (Frontiers in Energy Research, 2023)
In the last years, microbial electrochemical technologies have received increasing attention due to their promising environmental potential. However, the identification of the most suitable materials for further development of these technologies tends to be challenging, especially for operation under realistic wastewater conditions. The objective of the present work is to carry out a systematic comparison of six anode materials (stainless-steel wool, carbon paper, graphite felt, graphite plate, graphite foil, and stainless-steel mesh) for microbial electrolysis cells operated for the treatment of brewery wastewater and determine the best material of these in sight of its electrochemical performance. For this purpose, the medium was semisynthetic brewery wastewater of low buffer capacity and low conductivity. The results suggest, that the degree of fermentation and characteristics of the studied media have only a minor impact on the limiting current density of the bioanodes. Here, the limiting current density of microbial anodes with stainless steel wool (0.45 ± 0.07 mA∙cm-2), a not so extensively studied promising material, outperformed commonly used materials such as graphite felt, without evidence of corrosion.